Unraveling the genetic and molecular mechanisms of anthocyanin biosynthesis and accumulation in maize kernels - He, Mengting; Li, Jiansheng; Jin, Weiwei; Liu, Jingyan (Frontiers in Plant Science, 2026)
Anthocyanins are a class of water-soluble flavonoid pigments found in maize (Zea mays L.) kernels that exhibit strong antioxidant, anti-inflammatory, and anticancer properties, enhancing both the nutritional value and stress resilience of maize. Recent researches have made significant progress in elucidating the molecular mechanisms underlying anthocyanin accumulation in maize kernels. This review summarizes current knowledge on the genetic and molecular regulation of anthocyanin biosynthesis in maize kernels, highlighting the roles of structural and regulatory genes and the central MBW (MYB-bHLH-WD40) complex. It also integrates emerging insights into transcriptional regulation, signaling pathways, and stress-responsive mechanisms that collectively modulate anthocyanin accumulation in maize. These findings establish a coherent conceptual framework to guide future research and to facilitate the rational, targeted breeding of maize varieties enriched in anthocyanins. Overall, this review provides a solid theoretical foundation to support molecular breeding strategies aimed at developing anthocyanin-rich maize and to advance the industrial development and application of functional fresh maize.